Incorporation of rigid polyaromatic groups in polybenzimidazole-based polymeric ionic liquids: assertive effects on gas permeation properties - Shaligram, Sayali V.; Rewar, Anita S.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Polymer, 2016)
Polymeric ionic liquids (PILs) have emerged as promising membrane materials for CO2 separation. The present work is aimed at investigating the effects of incorporation of rigid polyaromatic hydrocarbons, viz., pyrene and anthracene, in polybenzimidazole-based PILs. The effects of substituent and anion variation on the gas permeation properties of PILs using pure gases were examined at 20 atm upstream pressure. The results were correlated with physical properties of PILs. The pyrene substituted PIL exhibited similar to 10 fold increase in CO2 permeability as compared to its precursor polymer PBI-BuI. The combination of a CO2 specific anion and bulky group substitution offered higher CO2 permeability as well as appreciable permselectivity than their structural analogue that was devoid of IL functionality. The permeation properties of present PILs were superior to those of conventional glassy polymers such as polysulfone, matrimid and polycarbonate which are widely studied for their gas permeation properties. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; membranes; Polymeric ionic liquids

Intrinsically microporous polyimides containing spirobisindane and phenazine units: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Dangat, Yuvraj; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A - Polymer Chemistry, 2018)
A new diamine containing spirobisindane and phenazine units, namely, 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[cyclopenta[b]phen azine]-7,7-diamine (TTSBIDA) was synthesized starting from commercially available 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethyl-1,1-spirobisindane (TTSBI). TTSBI was oxidized to 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[indene]-5,5,6,6-tet raone (TTSBIQ) which was subsequently condensed with 4-nitro-1,2-phenylenediamine to obtain 3,3,3,3-tetramethyl-7,7-dinitro-2,2,3,3-tetrahydro-1,1-spirobi[cyclope nta[b]phenazine] (TTSBIDN). TTSBIDN was converted into TTSBIDA by reduction of the nitro groups using hydrazine hydrate in the presence of Pd/C as the catalyst. A series of new polyimides of intrinsic microporosity (PIM-PIs) were synthesized by polycondensation of TTSBIDA with commercially available aromatic dianhydrides. PIM-PIs exhibited amorphous nature, high thermal stability (T-10>480 degrees C) and intrinsic microporosity (BET surface area=59-289 m(2)/g). The gas permeation characteristics of films of selected PIM-PIs were evaluated and they exhibited appreciable gas permeability as well as high selectivity. The CO2 and O-2 permeability of PIM-PIs were in the range 185.4-39.2 and 30.6-6.2 Barrer, respectively. Notably, polyimide derived from TTSBIDA and 4,4-(hexafluoroisopropylidene)diphthalic anhydride (PIM-PI-6FDA) exhibited high CO2 and O-2 permeability of 185.4 and 30.6 Barrer with CO2/CH4 and O-2/N-2 selectivity of 43.1 and 5.1, respectively. The data of PIM-PI-6FDA for CO2/CH4 and O-2/N-2 gas pairs were located near Robeson upper bound. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 766-775
Keywords: Gas permeability; intrinsic microporosity; polyimides; spirobisindane

Influence of hydrophilic/hydrophobic diols on the properties of polyurethane hydrogels: solvent-free one-pot synthesis - Divakaran, Anumon V.; Nair, Sanoop B.; Karambe, Shivani S.; Wadgaonkar, Prakash P.; Nair, Kiran Sukumaran; Badiger, Manohar V. (Journal of Materials Chemistry B, 2025)
Herein, we report the design and synthesis of bio-degradable porous polyurethane hydrogels by a green, solvent-free, one-pot technique that can withstand physiological mechanical loads and aid in tissue regeneration. The hydrophilic/hydrophobic nature of the hydrogel was tuned using diols such as polycaprolactone diol (PCL) and polycarbonate diol (PCD), in combination with polyethylene glycol (PEG, MW approximate to 4000 g mol-1), 4,4 `-methylene bis(cyclohexyl isocyanate) (H12MDI) and hexanetriol (HT), which served as crosslinking agents. The structural characterizations of the hydrogels were performed using FT-IR as well as 1H and 13C high resolution magic angle spinning nuclear magnetic resonance (HR-MAS) spectroscopy. The utilization of various diols in the synthesis of the hydrogels enabled precise control over crystallinity, pore sizes, and customization of mechanical and degradation properties. These hydrogels exhibited tensile strength in the range of 0.22-1.48 MPa, while their compressive strength varied from 0.92 to 29.3 MPa. In vitro degradation profiles in the presence and absence of the enzyme Amano lipase PS revealed that the degradation process is contingent upon the specific diol present in the hydrogel. Furthermore, preliminary in vitro biological experiments confirmed the biocompatibility of the gels, indicating their potential as suitable substrates for drug delivery applications. This diverse library of gels can be shaped into specific forms, highlighting their promising applications as scaffolds and implants in drug delivery systems and tissue engineering.